Effect of body mass index on survival after sudden cardiac arrest. Issue 1 (22nd January 2018) - Matinrazm, Sayna; Ladejobi, Adetola; Pasupula, Deepak Kumar; Javed, Awais; Durrani, Asad; Ahmad, Shahzad; Munir, Muhammad Bilal; Adelstein, Evan; Jain, Sandeep K.; Saba, Samir
Abstract : Background: Although elevated body mass index (BMI) is a risk factor for cardiac disease, patients with elevated BMI have better survival in the context of severe illness, a phenomenon termed the "obesity paradox." Hypothesis: Higher BMI is associated with lower mortality in sudden cardiac arrest (SCA) survivors. Methods: Data were collected on 1433 post‐SCA patients, discharged alive from the hospitals of the University of Pittsburgh Medical Center between 2002 and 2012. Of those, 1298 patients with documented BMI during the index hospitalization and follow‐up data constituted the study cohort. Results: In the overall cohort, 30 patients were underweight (BMI <18.5 kg/m 2 ), 312 had normal weight (BMI 18.5–24.9 kg/m 2 ), 417 were overweight (BMI 25.0–29.9 kg/m 2 ), and 539 were obese (BMI ≥30 kg/m 2 ). As expected, the prevalence of coronary artery disease, myocardial infarction, diabetes mellitus, and hypertension increased significantly with increasing BMI. Over a median follow‐up of 3.6 years, 602 (46%) patients died. Despite higher prevalence of cardiovascular comorbidities in more obese patients, a higher BMI was associated with lower all‐cause mortality on univariate analysis (hazard ratio: 0.86 per increase by 1 BMI category, 95% confidence interval: 0.78‐0.94, P = 0.002) and multivariate analysis after adjusting for unbalanced baseline comorbidities (hazard ratio: 0.86 per increase by 1 BMI category, 95% confidence interval: 0.77‐0.96, P = 0.009). Conclusions: Higher BMI is associated with lower all‐cause mortality in survivors of SCA, suggesting that the obesity paradox applies to the post‐arrest population. Further investigation into its mechanisms may inform the management of post‐SCA patients.